Can diffusion‐weighted imaging serve as a biomarker of fibrosis in pancreatic adenocarcinoma?. Issue 2 (2nd February 2017) - Hecht, Elizabeth M.; Liu, Michael Z.; Prince, Martin R.; Jambawalikar, Sachin; Remotti, Helen E.; Weisberg, Stuart W.; Garmon, Donald; Lopez‐Pintado, Sara; Woo, Yanghee; Kluger, Michael D.; Chabot, John A.
Abstract : Purpose: To assess the relationship between diffusion‐weighted imaging (DWI) and intravoxel incoherent motion (IVIM)‐derived quantitative parameters (apparent diffusion coefficient [ADC], perfusion fraction [f], Dslow, diffusion coefficient [D], and Dfast, pseudodiffusion coefficient [D*]) and histopathology in pancreatic adenocarcinoma (PAC). Materials and Methods: Subjects with suspected surgically resectable PAC were prospectively enrolled in this Health Insurance Portability and Accountability Act (HIPAA)‐compliant, Institutional Review Board‐approved study. Imaging was performed at 1.5T with a respiratory‐triggered echo planar DWI sequence using 10 b values. Two readers drew regions of interest (ROIs) over the tumor and adjacent nontumoral tissue. Monoexponential and biexponential fits were used to derive ADC2b, ADCall, f, D, and D*, which were compared to quantitative histopathology of fibrosis, mean vascular density, and cellularity. Two biexponential IVIM models were investigated and compared: 1) nonlinear least‐square fitting based on the Levenberg–Marquardt algorithm, and 2) linear fit using a fixed D* (20 mm 2 /s). Statistical analysis included Student's t ‐test, Pearson correlation ( P < 0.05 was considered significant), intraclass correlation, and coefficients of variance. Results: Twenty subjects with PAC were included in the final cohort. Negative correlation between D and fibrosis (Reader 2: r = –0.57 P = 0.01; pooled P = –0.46, P = 0.04) was observed with a trend toward positive correlation between f and fibrosis ( r = 0.44, P = 0.05). ADC2b was significantly lower in PAC with dense fibrosis than with loose fibrosis ADC2b ( P = 0.03). Inter‐ and intrareader agreement was excellent for ADC, D, and f. Conclusion: In PAC, D negatively correlates with fibrosis, with a trend toward positive correlation with f suggesting both perfusion and diffusion effects contribute to stromal desmoplasia. ADC2b is significantly lower in tumors with dense fibrosis and may serve as a biomarker of fibrosis architecture. Level of Evidence: 1 Technical Efficacy : Stage 2 J. MAGN. RESON. IMAGING 2017;46:393–402